A study on the use of femtosecond laser to perform surface polishing on a selective laser melting manufactured type 316L stainless steel - Ong, Kenrick Jin Hao (2019)
In this project, the author studied the use of femtosecond (fs) laser to perform laser polishing on the surface of interest of an additive manufactured 316L Stainless Steel sample. Selective Laser Melting (SLM) was the technique used to produce the sample. The laser is an ultra-short pulsed Ti:Sapphire diode laser which removes material by ablation. The problem is to check the effects of femtosecond (fs) laser used on laser polishing of a SLM SS316L sample. The parameters, mainly the power setting of the laser and the scanning speed, were used to observe the effects. Two rows of laser polished spots were made. Row ‘P’ consists of laser polished spots with constant scanning speed of 50mm/s while the power setting was set at various percentage: 20%, 40%, 60%, 80%, 100% of the 1.5W produced by the laser. Row ‘V’ consists of laser polished spots with constant power setting at 80% of the 1.5W laser power while scanning speed was set at various speeds (in mm/s): 10, 30, 70, 100, 150. The results were obtained from the effects of the different laser parameters applied on polishing the surface of interest. Laser-induced periodic ripples were formed and radiated outwards from an unfused SS316L particulate on the laser polished spots. In Row ‘V’, the ripples grew larger as the power setting was increased and in Row ‘V’, the growth took place as the scanned speed was reduced. Significant effects could be seen very prominently in Row ‘V’ laser polished spots, hence a further analysis on surface roughness was chosen on Row ‘V’. It was observed that the formation of micro-grooves began at 80% power setting and scanning speed of 30mm/s. At same power setting and slower scanning speed of 10mm/s, the evolution of the micro-grooves grew more and larger with greater depth. It appeared to be the effect of more material getting ablated in the depth direction surrounding the particulate where the laser beam was directed to the surface for a longer period. Surface roughness measurements of Row ‘V’ showed no significant changes to the roughness compared to the original surface.